FORMATION OF AN ACTION PLAN AIMED AT PRROMOTING TOURISTS DESTINATIONS - Glinkina, Elena; Allanina, Liliya; Yakhyaeva, Marhat; Mushrub, Vladimir; Stepanova, Diana (Revista Inclusiones, 2020)
The high level of international competition in the world tourism market forces Russia to make great efforts for attracting tourists to the country, use new technologies for promoting national tourism products and invest significant financial resources in the promotion of tourist destinations. It is necessary to promote Russia as a whole as a destination, but a tourism product is formed in certain regions and localities. Visitors, arriving in Russia as a destination, for the most part, consume a regional tourism product, i.e. are in regional destinations. The quality and quantity of regional tourism products determine the success of promoting the entire destination country. Therefore, it is important to create regional destinations that offer their tourism products, which are part of the national tourism product.